2013
DOI: 10.5625/lar.2013.29.3.168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogen on food intake, serum leptin levels and leptin mRNA expression in adipose tissue of female rats

Abstract: The integration of metabolism and reproduction involves complex interactions of hypothalamic neuropeptides with metabolic hormones, fuels, and sex steroids. Of these, estrogen influences food intake, body weight, and the accumulation and distribution of adipose tissue. In this study, the effects of estrogen on food intake, serum leptin levels, and leptin mRNA expression were evaluated in ovariectomized rats. Seven-week-old female Wistar-Imamichi rats were ovariectomized and divided into three treatment groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 28 publications
(35 reference statements)
0
25
0
Order By: Relevance
“…Similarly, estrogen levels are linked with appetite. Animal studies have found that estrogen treatment leads to significantly higher serum leptin levels and lower food intake (28). Klump et al showed that increases in DEBQ Emotional Eating Scale scores were associated with decreases in estradiol and increases in progesterone across the menstrual cycle among women in community samples (23).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, estrogen levels are linked with appetite. Animal studies have found that estrogen treatment leads to significantly higher serum leptin levels and lower food intake (28). Klump et al showed that increases in DEBQ Emotional Eating Scale scores were associated with decreases in estradiol and increases in progesterone across the menstrual cycle among women in community samples (23).…”
Section: Discussionmentioning
confidence: 99%
“…18 Estrogen is also known have a role in the regulation of orexigenic neuropeptides such as NPY and grelin, and anorexigenic neuropeptides like insulin, leptin and serotonin. 19 In addition, studies reveals that estrogen deficiency causes excessive production of NPY in the hypothalamus and central leptin sensitivity disorders that causes an increase food intake and contributes to obesity. The results of paired t-test showed that there was a significant increase in the value of the index Lee before and after ovariectomy both in ovariectomy and non ovariectomy group.…”
Section: -17mentioning
confidence: 99%
“…These observations suggest a key role of estrogens in lipid distribution and metabolism homeostasis. In rodents, E2 treatment opposes obesity in both males and females (83) and reduces food intake, increases lipolysis and physical activity (89)(90)(91).…”
Section: Lxr Function: Sex Differencesmentioning
confidence: 99%